2007
DOI: 10.1007/s10549-007-9694-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and molecular subtypes of breast cancer in Nigeria

Abstract: We conclude that there is no difference in the pattern of hormone receptors in breast cancer patients of African origin compared to other populations and urge more use of hormone manipulation for management of breast cancer in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
108
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 25 publications
17
108
12
Order By: Relevance
“…The study concluded that the diferences between the Sudanese and the Italian breast cancer series relected stage at diagnosis rather than intrinsic biological characteristics [33]. This was in accordance with data reported for a breast cancer series from Nigeria, where Adebamowo and collaborators reported a high frequency of hormone receptor-positive cases, when the histopathology samples were collected under rigorous control for appropriate ixation [50]. On the contrary, studies that compared extensive series of African-American and European-American breast cancer patients found associations between aggressive estrogen receptor (ER)-negative breast cancer and both younger age at diagnosis and black ethnicity [19,40,48].…”
Section: Major Clinicopathological Features Of Breast Cancer In Sudansupporting
confidence: 86%
“…The study concluded that the diferences between the Sudanese and the Italian breast cancer series relected stage at diagnosis rather than intrinsic biological characteristics [33]. This was in accordance with data reported for a breast cancer series from Nigeria, where Adebamowo and collaborators reported a high frequency of hormone receptor-positive cases, when the histopathology samples were collected under rigorous control for appropriate ixation [50]. On the contrary, studies that compared extensive series of African-American and European-American breast cancer patients found associations between aggressive estrogen receptor (ER)-negative breast cancer and both younger age at diagnosis and black ethnicity [19,40,48].…”
Section: Major Clinicopathological Features Of Breast Cancer In Sudansupporting
confidence: 86%
“…(16) Early age at onset and aggressive clinical features have frequently been documented in clinical series from Africa and case series from several centers in Africa have reported that hormone receptor-negative cases are predominant (17)(18)(19), for example, only 25% of cases in a large multicenter series of patients from West Africa were ERpositive, less than half that observed in the U.S. Black (20,21). However, these findings from Africa were based on archival materials and the role of antigen degradation and false negative results could not be ruled out (18). Indeed, a more recent prospective case-series study in South African Black women found that only 35% of breast cancer cases were ER negative (22), which was comparable with those which had been reported in U.S. Black women (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a study of indigenous West African women found that the proportions of luminal A, luminal B, HER2 type, basal-like, and unclassified tumors were 27%, 2%, 15%, 27%, and 28%, respectively [14]. Another study from Nigeria found that 77.6% were luminal type A, 2.6% luminal type B, 15.8% basal-like, and the remaining 4.0% HER2 type [15] A study from North Africa (Egypt) reported 44% luminal A, 26.6% luminal B, 11.8% HER2 type, 11.3% basal-like, and 7.9% unclassified [16], while a study from Sudan found a high proportion of ER-and PR-positive tumours [17] and lower basal-like (10%) phenotypes [18]. This last study did not assess the HER2 type of breast carcinoma.…”
Section: Introductionmentioning
confidence: 93%